Exploring Specialty Selection and Influencing Factors among Medical Students and Postgraduates: An Observational Study: Specialty Selection and Influencing Factors among Medical Students - Arif, Muhammad Maaz; Nisar , Wardah; Agha , Khadija; Qureshi, Muzammil Ghaffar; Mansoor, Amen; Malik, Asad Ullah; Khokhar, Muhammad Sohaib; Awan, Fatima; Khwaja, Sarah Irfan; Parveen, Aqsa (Pakistan Journal of Health Sciences, 2023)
Medical students are driven by interest and influenced by factors like early exposure, training, environment, teaching, role models, rewards, appreciation, patient feedback, and mentorship. Gender also impacts specialty choices. Students’ career choices shape the future workforce. Objective: To explore interests and factors influencing specialty choice among post graduate trainees and final year students, aiming to guide informed career decisions and address inadequate recruitment in specialties. Methods: This study was an observational cross-sectional study conducted at Fatima Memorial Hospital and college. Data were collected from 163 participants via online questionnaire using non-convenience sampling. Analysis was conducted using SPSS software, including frequencies, percentages, averages and t-test to assess statistical significances. Results: Study finds strong preference for clinical subjects among final year and postgraduate students. Divergence among specialty selection was seen as final year students favor general surgery, while postgraduate trainees lean towards pediatrics medicine. Prestige and social responsibility were common influential key factors, with salary benefits impacting more the final year students and specialty prestige, social responsibility and research opportunities weighing on postgraduate trainees were seen. The research also explores that family influence for final year students and teachers and senior doctors for postgraduate trainees in specialty selection. Conclusions: In conclusion, final year and postgraduate trainees prefer clinical specialties like general surgery and pediatrics, driven by considerations of future salary, working hours, and social responsibility. Family, teachers, and senior colleagues play crucial roles in specialty selection decisions.